2016
DOI: 10.1016/j.ejphar.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical factors associated with the antidepressant-like effect of flavonoid chrysin in chronically stressed mice

Abstract: Chrysin is a flavonoid which is found in bee propolis, honey and various plants. Antidepressant-like effect of chrysin in chronically stressed mice was previously demonstrated by our group. Conversely, neurochemical factors associated with this effect require further investigations. Thus, we investigated the possible involvement of pro-inflammatory cytokines, kynurenine pathway (KP), 5-hydroxytryptamine (5-HT) metabolism and caspases activities in the effect of chrysin in mice exposed to unpredictable chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…, 28 days), similar to antidepressant fluoxetine (10 mg/kg, p.o. , 28 days), increases serotonin concentration and reduces the indoleamine-2,3-dioxygenase and caspases 3 and 9 activities in the prefrontal cortex and hippocampus in C57B/6J mice subjected to CUMS, which was associated with the antidepressant-like effect detected in the tail suspension test [ 118 ], with the participation of BDNF. Similarly, the administration of 20 and 40 mg/kg of the flavonoid orientin for 21 days also produced antidepressant-like effects in mice that were subjected to CUMS, and this effect was associated with the activation of BDNF and an increase in serotonin and norepinephrine concentration in the hippocampus and cerebral cortex [ 40 ].…”
Section: Antidepressant-like Effects Of Flavonoids Isolated From Pmentioning
confidence: 99%
“…, 28 days), similar to antidepressant fluoxetine (10 mg/kg, p.o. , 28 days), increases serotonin concentration and reduces the indoleamine-2,3-dioxygenase and caspases 3 and 9 activities in the prefrontal cortex and hippocampus in C57B/6J mice subjected to CUMS, which was associated with the antidepressant-like effect detected in the tail suspension test [ 118 ], with the participation of BDNF. Similarly, the administration of 20 and 40 mg/kg of the flavonoid orientin for 21 days also produced antidepressant-like effects in mice that were subjected to CUMS, and this effect was associated with the activation of BDNF and an increase in serotonin and norepinephrine concentration in the hippocampus and cerebral cortex [ 40 ].…”
Section: Antidepressant-like Effects Of Flavonoids Isolated From Pmentioning
confidence: 99%
“…In another study done by the same research group members [ 46 ], they showed that the treatment with chrysin caused the attenuation of depressive-like behavior and hippocampal changes in olfactory bulbectomized mice, reinforcing that BDNF plays an important role in the antidepressant effect of this flavonoid. Further, Filho et al [ 47 ] likewise analyzed the neurochemical parameters correlated with the antidepressant property of chrysin in mice exposed to unpredictable chronic stress. The authors suggested an association existing between the antidepressant-like action of chrysin and the proinflammatory cytokines synthesis, 5-hydroxytryptamine metabolism, kynurenine pathway, and caspases activities.…”
Section: Resultsmentioning
confidence: 99%
“…Unpredictable chronic stress in an animal model also involves synthesis of pro-inflammatory cytokines, kynurenine pathway (KP), 5-hydroxytryptamine metabolism and caspase activities. Phenolics can reduce the levels or metabolism of these molecules and their activities (Filho et al, 2016 ). On the other hand, phenolics can prevent age-associated memory loss by scavenging free radicals and modulating BDNF levels (Souza et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%